Parvalbumin alters mitochondrial dynamics and affects cell morphology - Lichvarova, Lucia (Cell Mol Life Sci, 2018)
The Ca(2+)-binding protein parvalbumin (PV) and mitochondria play important roles in Ca(2+) signaling, buffering and sequestration. Antagonistic regulation of PV and mitochondrial volume is observed in in vitro and in vivo model systems. Changes in mitochondrial morphology, mitochondrial volume and dynamics (fusion, fission, mitophagy) resulting from modulation of PV were investigated in MDCK epithelial cells with stable overexpression/downregulation of PV. Increased PV levels resulted in smaller, roundish cells and shorter mitochondria, the latter phenomenon related to reduced fusion rates and decreased expression of genes involved in mitochondrial fusion. PV-overexpressing cells displayed increased mitophagy, a likely cause for the decreased mitochondrial volumes and the smaller overall cell size. Cells showed lower mobility in vitro, paralleled by reduced protrusions. Constitutive PV down-regulation in PV-overexpressing cells reverted mitochondrial morphology and fractional volume to the state present in control MDCK cells, resulting from increased mitochondrial movement and augmented fusion rates. PV-modulated, bi-directional and reversible mitochondrial dynamics are key to regulation of mitochondrial volume. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00018-018-2921-x) contains supplementary material, which is available to authorized users.